Physical, chemical, and biological investigations of SrTiO3‐Ca10(PO4)6(OH)2 composites for biomedical applications. Issue 3 (9th July 2021) - Das, Apurba; Bhardwaj, Aman; Rabha, Susmita; Pandey, Lalit M.; Dobbidi, Pamu
Abstract: In this article, the interplay between structural, electrical, and surface properties in determining the collective behavior of C a 10 ( P O 4 ) 6 ( O H ) 2 (hydroxyapatite, HAP) and S r T i O 3 (strontium titanate, ST) composites was reported. The monoliths HAP and ST were synthesized using sol‐gel and solid‐state reaction, respectively, and were mixed in different atomic concentrations (20, 40, 60, and 80 at.%) to prepare a series of composites. The prepared composites were then subjected to x‐ray diffraction (XRD) and Raman analysis for probing the microstructural aspects. The analysis revealed no evidence of a phase that the reaction between the two monoliths might form. The crystallite sizes were in the range of 27.2–37.3 nm, and it increased with the content of ST in the composites. The Raman analysis revealed the presence of rutile T i O 2 that was later found to be the link in the display of bone‐like apatite nucleation ability in the monolith ST and its composites. The FESEM analysis revealed that the grain sizes were 64–144 nm between the monoliths and were found to follow a similar trend to the crystallite size. The dielectric constant ( ϵ r ) varied with temperature ranging from 5 to 35 (1 MHz) at 310 K for all the specimens. The dependence of ϵ r on the grain size of the composites followed a nearly exponential relation. The bone‐like apatite forming ability of the composites was studied by incubating the specimens in simulated body fluid (SBF). Additionally, the cytocompatibility (MG63 cell lines) and protein adsorption (bovine serum albumin [BSA]) of the selected specimens were also studied to comprehensively understand the delicate relationship between the electrical and biological properties. The protein adsorption was primarily related to the surface charge, and its dependence was found to be linear. Additionally, the ϵ r of the composites was ≤35, which compliments the protein adsorption behavior of the specimens. The amount of adsorbed protein for all the specimens considered in this study was in the range of 3–32 μ g/ml. Furthermore, the specimens exhibited excellent cell viability of more than 90%. Based on the physical and biological investigations, 20H‐80S was established as the best specimen that blends the characteristic feature of both the monoliths. Finally, the TEM and STEM mapping of the best specimen, projecting the suitability of 20H‐80S in the design of electrically active scaffolds and possibly bioelectrets for biomedical applications, was also studied. Abstract : A schematic representation of the idea presented in the article. The motivation for the article is to present a correlation of the electrical and biological properties of electrically active ceramics from a perspective of biomedical applications.